Mysterious syndrome causing high mortality in wild brown trout in Eastern Switzerland, pathology and search for a possible cause. Issue 10 (24th August 2020) - Schmidt‐Posthaus, Heike; Koch, Michel; Seuberlich, Torsten; Birrer, Christoph; Hirschi, Regula; Kugler, Michael
Abstract: Since 2016, annually occurring species‐specific die‐offs of brown trout ( Salmo trutta fario ) occurred in the Thur River, situated in the Eastern part of Switzerland. These events lead to drastically reduced population densities in the impacted river regions. Clinical signs in brown trout and mortality were restricted to few weeks in August/September. To characterize the syndrome and to find possible causes, from end of March to November 2018, one‐year‐old brown trout ( Salmo trutta fario ) and rainbow trout ( Oncorhynchus mykiss ) were exposed to water from Thur River, fish were sampled regularly and screened for infectious agents, including viral metagenomics, and pathology was described. Starting approximately four months post‐exposure, brown trout showed severe lymphohistiocytic pancarditis and necrotizing and haemorrhagic hepatitis. These lesions were recorded until the end of the experiment in November. Rainbow trout were not affected at any point in time. No infectious agents could be identified so far as cause of disease, especially no viral aetiology. Even if pathogenesis and pathology point in the direction of an infectious agent, a causative relationship could not be confirmed and aetiology remains unclear.